Nonalcoholic fatty pancreas disease in obese children: case reports - Wasilewska, Natalia; Bobrus-Chociej, Anna; Filimoniuk, Aleksandra; Kucharska, Magdalena; Cudowska, Beata; Siergiejko, Grzegorz; Lebensztejn, Dariusz (Pediatria Polska - Polish Journal of Paediatrics, 2019)
Nonalcoholic fatty pancreas disease (NAFPD) is defined as excessive lipid accumulation in the pancreas, which occurs in obese patients. Similarly to nonalcoholic fatty liver disease (NAFLD), it can progress towards more advanced stage – nonalcoholic steatopancreatitis (NASP). However, the epidemiology, pathogenesis, including its relation to metabolic syndrome (MetS), and treatment recommendations have not been fully established yet. The aim of our study was to present three cases of NAFPD in obese children. We present their examination, diagnostic process, laboratory and imaging study results to note that not only NAFLD but also NAFPD can coexist with childhood obesity.